Shakespeare's words a glossary and language companion - Crystal, David; Crystal, Ben (London Penguin, 2002)
A vital resource for scholars, students and actors, this book contains glosses and quotes for over 14,000 words that could be misunderstood by or are unknown to a modern audience. Displayed panels look at such areas of Shakespeare's language as greetings, swear-words and terms of address. Plot summaries are included for all Shakespeare's plays and on the facing page is a unique diagramatic representation of the relationships within each play.
Keywords: Shakespeare, William, 1564-1616 -- Language -- Glossaries, etc; English language -- Early modern, 1500-1700 -- Glossaries